(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
The article reflects on how artists can develop ways of (re)telling the city through the Theater of Documentary Objects, considering the spectator as co-author of the artistic experience. Focusing on the virtual workshop ArteFatos(?), from 2022, I seek to analyze the process of opening personal memories at a collective level, thinking about the city through the recording space embodied by the documentary scene with objects. By exploring narratives about material goods that resist time thanks to an affectionate relationship with their owners, the project’s main provocative material was twelve biographical accounts of residents of Araranguá/SC. Thus, through different artistic procedures, the work offers paths for reflection on the city and the search for a participating public.